The relationship between self confidence and competitive anxiety among male handball player during KARISMA 2019 / Muhammad Amirul Muhammad Khalil - Muhammad Khalil, Muhammad Amirul (Faculty of Sport Sciences and Recreation, 2020)
The purpose of this study was to identify the relationship between self-confidence and competitive anxiety among male handball player during KARISMA 2019. A total of 120 male subjects from handball team participated in KARISMA 2019 were selected through purposive sampling which aged 18 to 23. The participants completed the CSAI-2 questionnaire prior to the game. The result showed that self-confidence correlated negatively to subcomponents of competitive anxiety which are cognitive anxiety and somatic anxiety. It is possible that self-confident was an effective coping strategies and have perceived ability to control the anxiety levels. As conclusion, this finding suggested that it can be helpful as self confidence promotes coping strategies and stress management.